Identification of Compounds That Promote Readthrough of Premature Termination Codons in the CFTR. (February 2021) - Smith, Emery; Dukovski, Danijela; Shumate, Justin; Scampavia, Louis; Miller, John P.; Spicer, Timothy P.
Cystic fibrosis (CF) is caused by a mutation of the Cystic Fibrosis Transmembrane Conductance Regulator ( CFTR ) gene, which disrupts an ion channel involved in hydration maintenance via anion homeostasis. Nearly 5% of CF patients possess one or more copies of the G542X allele, which results in a stop codon at residue 542, preventing full-length CFTR protein synthesis. Identifying small-molecule modulators of mutant CFTR biosynthesis that affect the readthrough of this and other premature termination codons to synthesize a fully functional CFTR protein represents a novel target area of drug discovery. We describe the implementation and integration for large-scale screening of a homogeneous, 1536-well functional G542X-CFTR readthrough assay. The assay uses HEK 293 cells engineered to overexpress the G542X-CFTR mutant, whose functional activity is monitored with a membrane potential dye. Cells are co-incubated with a CFTR amplifier and CFTR corrector to maximize mRNA levels and trafficking of CFTR to the cell surface. Compounds that allow translational readthrough and synthesis of functional CFTR chloride channels are reflected by changes in membrane potential in response to cAMP stimulation with forskolin and CFTR channel potentiation with genistein. Assay statistics yielded Z′ values of 0.69 ± 0.06. As further evidence of its suitability for high-throughput screening, we completed automated screening of approximately 666, 000 compounds, identifying 7761 initial hits. Following secondary and tertiary assays, we identified 188 confirmed hit compounds with low and submicromolar potencies. Thus, this approach takes advantage of a phenotypic screen with high-throughput scalability to identify new small-molecule G542X-CFTR readthrough modulators.